Preliminary study on the preparation of bio-organic fertilizer from sauce-flavor Baijiu distillers' grains and fertilizer efficiency - ZENG Xiang, LI Xiutong, JIANG Youfeng, XIA Xuchun, CHENG Lifangyu, WANG Xiaodan (Zhongguo niangzao)
In order to realize the resource utilization of Baijiu distillers' grains, two kinds of distillers' grains organic fertilizer (treatment group 1 organic fertilizer and treatment group 2 organic fertilizer) were prepared by distillers' grains mixed fermented with cellulose degrading strains A5 and B2(1∶1). Then, the bio-organic fertilizers (No.1 bio-organic fertilizer and No.2 bio-organic fertilizer) were prepared by the inoculation with the screened nitrogen fixation bacteria N1, phosphorus solubilizing bacteria P1 and P2 into distillers' grains organic fertilizer. The indexes including moisture, temperature, pH and germination index in the composting process of distillers' grains organic fertilizer were detected, and the quality of distillers' grains organic fertilizer and bio-organic fertilizer was analyzed. The results showed that the addition of cellulose-degrading strains had no effect on the trend of water, temperature and pH, but could increase the germination index of distillers' grain organic fertilizer. The germination rate and germination index of distillers' grains organic fertilizer in treatment group 1 and treatment group 2 were 98.63%, 90.64%, 97.72% and 79.86%, respectively. The germination rate of No. 1 and No. 2 bio-organic fertilizers were 100% and 95%, and the germination index was 82.99% and 90.40%, respectively. The germination rate of bio-organic fertilizers was higher than that of distiller's grains organic fertilizers. Their physicochemical indexes were in line with relevant industry standards. Compared with no bio-organic fertilizer addition, the growth of sorghum seedlings could be promoted when the bio-organic fertilizer No.1 addition was 10%-80%, and the growth of sorghum seedlings was better when the bio-organic fertilizer addition was 40%.